2007
DOI: 10.1016/j.bbamcr.2006.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the actin cytoskeleton in cancer cell migration and invasion

Abstract: Malignant cancer cells utilize their intrinsic migratory ability to invade adjacent tissues and the vasculature, and ultimately to metastasize. Cell migration is the sum of multi-step processes initiated by the formation of membrane protrusions in response to migratory and chemotactic stimuli. The driving force for membrane protrusion is localized polymerization of submembrane actin filaments. Recently, several studies revealed that molecules that link migratory signals to the actin cytoskeleton are upregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
857
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 994 publications
(891 citation statements)
references
References 117 publications
27
857
0
7
Order By: Relevance
“…The actin assembly and dendritic nucleation involved in the formation of both lamellipodia and invadopodia have been shown to require the actin nucleator Arp2/3, its activator, N-WASP and the stabilizing actin binding protein cortactin [13][14][15][16]. Conversely, the relatively transient and less substantial filopodial membrane extension or ruffle which functions as a pseudo sensory organ that assimilates extracellular stimuli, is made up of bundles of long, cross-linked parallel actin filaments that are nucleated and elongated by the formin family protein, mDia1 and mDia2/DRF3 (Figure 1.1 A, D & E) [13][14][15][16][17][18].…”
Section: The Cytoskeleton and Cellular Extensionmentioning
confidence: 99%
See 2 more Smart Citations
“…The actin assembly and dendritic nucleation involved in the formation of both lamellipodia and invadopodia have been shown to require the actin nucleator Arp2/3, its activator, N-WASP and the stabilizing actin binding protein cortactin [13][14][15][16]. Conversely, the relatively transient and less substantial filopodial membrane extension or ruffle which functions as a pseudo sensory organ that assimilates extracellular stimuli, is made up of bundles of long, cross-linked parallel actin filaments that are nucleated and elongated by the formin family protein, mDia1 and mDia2/DRF3 (Figure 1.1 A, D & E) [13][14][15][16][17][18].…”
Section: The Cytoskeleton and Cellular Extensionmentioning
confidence: 99%
“…Conversely, the relatively transient and less substantial filopodial membrane extension or ruffle which functions as a pseudo sensory organ that assimilates extracellular stimuli, is made up of bundles of long, cross-linked parallel actin filaments that are nucleated and elongated by the formin family protein, mDia1 and mDia2/DRF3 (Figure 1.1 A, D & E) [13][14][15][16][17][18].…”
Section: The Cytoskeleton and Cellular Extensionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that force sensing and substrate stiffness define the formation and turnover of the adhesions to the extracellular matrix and determine the speed of migration, as well as cell shape and ability to differentiate (Engler et al, 2006). Loss of force sensing accompanies adhesive and migratory defects in vitro and in situ, including oncogenic transformation and cancer metastases, closely correlated with the ability of cells for substrate-independent growth (Kedrin et al, 2007;Yamaguchi and Condeelis, 2007).…”
Section: Extracellular Matrix and Force Sensing: Paving The Pathways mentioning
confidence: 99%
“…Motility is initiated by protrusion of the leading edge of the cell, resulting in the production of polarised lamellipodia oriented towards the direction of movement (Yamaguchi and Condeelis, 2007). Cortactin is a ubiquitously expressed Src substrate that engages in several protein -protein interactions that may be functionally relevant to tumoral progression.…”
mentioning
confidence: 99%